"You, as of Now, Are Someone Else!": Minoritization, Settler Colonialism, and Indigenous Health. Issue 1 (2nd January 2023) - Tanous, Osama
Abstract: This article challenges the dominant notion that the health of Palestinians inside the Green Line can be framed or understood as an issue of "minority health" characterized by a "gap" that needs bridging in order for health equity to be attained. It situates the health of Palestinians in Israel within the realm of Indigenous health and claims that the settler-colonial nature of the state of Israel, the minoritization of Palestinians, and their depeasantization through land policies and water infrastructures have produced an Indigenous community alienated from its lands and from nature. These processes, I argue, contribute to adverse health outcomes that are then reported simply as "minority health" phenomena, chalked up to behavioral patterns or biology. The article seeks to challenge the entire notion of "minority health" as a purportedly neutral statistical unit and to launch a conversation on the health effects of minoritization in settler-colonial contexts.